HISTORICAL AND LEGAL ANALYSIS OF THE INSTRUMENTS OF THE PRESIDENT’S POWER IN THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents a comprehensive historical and legal analysis of the formation of the institution of the President in the Kyrgyz Republic and the exercise of power by him under the Constitution. The current issues of constitutional reform are also analyzed. Other concepts are reflected, namely the system of checks and balances, the coordinated interaction of authorities, without which the evolutionary development of the Kyrgyz Republic is impossible.
Keywords: сonstitution, President, Parliament, Government, interaction, power, rule of law, rights and freedoms, sovereignty, source of power, referendum, constitutional reform